(untitled) (Psychology Travelogs, 2023)
The study is dedicated to the problem of gender characteristics of emotional response to war, as well as to the identification of gender characteristics and differences in the experience of various mental problems, which are the consequences and manifestations of emotional response. The purpose of the article is a theoretical analysis of gender differences in emotional response to war. To achieve this goal, the works of domestic and foreign researchers were analyzed. Men and women are sexes that have certain differences in the context of experiencing different events in terms of emotions. In addition, both sexes are distinguished by different emotionality, which may affect their emotional response to war. War is closely related to the constant experience of fear, anger and sadness, which can lead to certain mental disorders, which can be closely related to the emotional response, emotionality of a person, his emotional intelligence and his emotional experience of certain events, mostly negative. In general, women are more emotional than men are. Women are more prone to empathy, more expressive, that is why they are more prone to complex emotional experience of negative emotions during war. However, men tend to suppress their own emotions, so such actions during war can lead to negative consequences, such as high levels of anxiety, fear, emotional burnout, etc. Women more than men are exposed to certain negative emotional changes in the process of overcoming stress, which indicates that women are characterized by less stress resistance, therefore they are prone to certain negative mental states that arise as a result of experiencing stressful situations. The article reviews such emotional reactions and states of men and women during the war as stress, anxiety, irritation, fear, anger, post-traumatic stress disorder.